Comparative Genomics Reveal a Flagellar System, a Type VI Secretion System and Plant Growth-Promoting Gene Clusters Unique to the Endophytic Bacterium Kosakonia radicincitans - Becker, Matthias; Patz, Sascha; Becker, Yvonne; Berger, Beatrice; Drungowski, Mario; Bunk, Boyke; Overmann, Jörg; Spröer, Cathrin; Reetz, Jochen; Tchuisseu Tchakounte, Gylaine V.; Ruppel, Silke (Frontiers in Microbiology, 2018)
The recent worldwide discovery of plant growth-promoting Kosakonia radicincitans in a large variety of crop plants suggests that this species confers significant influence on plants, both in terms of yield increase and product quality improvement. We provide an approach on comparative genomics which helps to unravel the basis for K. radicincitans’ motility, competitiveness and plant growth promoting capacities. We discovered that K. radicincitans carries multiple copies of complex gene clusters, among them two flagellar systems and three type VI secretion systems, indicating that host invasion may be facilitated by different flagella, and bacterial competitor suppression by effector proteins. We found a large plasmid in K. radicincitans DSM 16656T, the species type strain, that confers the potential to exploit plant-derived carbon sources. We propose that multiple copies of complex gene clusters in K. radicincitans are metabolically expensive but provide competitive advantage over other bacterial strains in nutrient-rich environments. The comparison of the DSM 16656T genome to genomes of other genera of enteric PGPB exhibits traits unique to DSM 16656T and K. radicincitans, respectively, and traits shared between genera. We used the output of the in silico analysis for predicting the purpose of genomic features unique to K. radicincitans and tested our hypotheses by in vivo experiments. This information will facilitate the future search for promising candidates of PGPB for sustainable crop production.